Clinical outcome of frozen blastocyst transfer; single vs. double transfer - Yanaihara, Atsushi (Springer US, 2008)
PURPOSE: Frozen embryo transfer has been established as an indispensable ART procedure for both the effective use of surplus embryos and the prevention of ovarian hyperstimulation syndrome. The frequency of frozen embryo transfer is increasing in our clinic, and we report that frozen embryo transfer is effective for patients with repeat failures. We present our clinical outcome of frozen blastocyst transfer (FBT). METHODS: In 2006, 470 patients received FBT (562 cycles (IVF: 354 cycles; ICSI: 208 cycles)). One frozen blastocyst was transferred in 412 cycles (335 patients) and two blastocysts were transferred in 150 cycles (135 patients). Assisted hatching was performed in all cases. RESULTS: In 412 cycles (average age: 34.6 years) who received a single FBT, the rate of clinical pregnancy per cycle was 40.7%, the live birth rate was 29.1%, the abortion rate was 21.6%, the ectopic pregnancy rate was 1.2%, the frequency of monochorionic twins was 2.3%, and the cesarean section rate was 38.3%. In 150 cycles (average patient age 34.8 years) who received two FBTs, the clinical pregnancy rate was 46%, the live birth rate was 35.3%, the abortion rate was 16.3%, the ectopic pregnancy rate was 4.4%, the frequency of twins was 15.9% and the cesarean section rate was 39.6%. A significant difference in the ectopic pregnancy rate and the twinning rate was found between single transfers and double transfers (P < 0.05). When IVF and ICSI were compared, there was no statistically significant difference in the abortion rate, the ectopic pregnancy rate, and the cesarean section rate. CONCLUSIONS: The clinical pregnancy rate was similar for the transfer of one and two blastocysts. Single FBT decreases obstetrical risk without reducing the pregnancy rate.